Desarrollo de software de predicción de carga de energía basado en Machine Learning - Cuadros García, Paquita Alejandra (Machala: Universidad Técnica de Machala, 2023)
This research focuses on the development of an electrical power charge prediction system to validate power behavior using Convolutional Neural Networks (CNN), Artificial Neural Networks (ANN) and Long and Short Term Memory (LSTM). Metrics such as the Mean Absolute Percentage Error (MAPE) and the coefficient of determination (R2) are used to assess the accuracy of the predictions. The methodology used in the research is mixed, combining quantitative and qualitative approaches. The CRISP-DM methodology is followed, which consists of different stages such as understanding the business, understanding the data, data preparation, modeling, evaluation and use. The research approach is experimental, where variables are manipulated and monitored according to the established metrics. In addition, the study is carried out in a descriptive context, presenting and analyzing the relevant variables. The main objective of the work is to develop an electric power charge prediction system using the CNN, ANN and LSTM neural networks, and to evaluate its performance using the MAPE and R2 metrics. The purpose is to improve the predictability of electrical power load and provide reliable and accurate results. Tests and experiments are carried out to compare the performance of the different models and techniques used. It seeks to identify the most efficient and effective model in the prediction of the electric power load. In summary, the thesis focuses on the development of an electrical energy prediction system using CNN, ANN and LSTM neural networks. Metrics such as MAPE and R2 are used, and the CRISP-DM methodology is followed. The research is carried out using a mixed approach, with an experimental and descriptive approach. The goal is to improve the accuracy and reliability of electrical power load forecasting, which may have important applications in efficient power planning and management.
La presente investigación se centra en el desarrollo de un sistema de predicción de carga de energía eléctrica para validar el comportamiento energético utilizando redes neuronales convolucionales (CNN), redes neuronales artificiales (ANN) y la memoria de corto y largo plazo (LSTM). Se emplean métricas como el Error Porcentual Absoluto Medio (MAPE) y el coeficiente de determinación (R2) para evaluar la precisión de las predicciones. La metodología utilizada en la investigación es mixta, combinando enfoques cuantitativos y cualitativos. Se sigue la metodología CRISP-DM, que consta de diferentes etapas como comprensión del negocio, comprensión de los datos, preparación de los datos, modelado, evaluación y despliegue. El enfoque de investigación es experimental, donde se manipulan y monitorean variables de acuerdo a las métricas establecidas. Además, el estudio se desarrolla en un contexto descriptivo, presentando y analizando las variables relevantes. El objetivo principal del trabajo es desarrollar un sistema de predicción de carga de energía eléctrica utilizando las redes neuronales CNN, ANN y LSTM, y evaluar su desempeño utilizando las métricas MAPE y R2. El propósito es mejorar la capacidad de predicción de la carga de energía eléctrica y proporcionar resultados confiables y precisos. Se realizan pruebas y experimentos para comparar el rendimiento de los diferentes modelos y técnicas utilizadas. Se busca identificar el modelo más eficiente y efectivo en la predicción de la carga de energía eléctrica.
Keywords: APRENDIZAJE AUTOMATICO; APRENDIZAJE AUTOMATICO; RED NEURONAL; PREDICCION DE CARGA ELECTRICA; SOFTWARE; PHYTON